# 6(k-5)-(1-5k)=10k

## Simple and best practice solution for 6(k-5)-(1-5k)=10k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6(k-5)-(1-5k)=10k equation:

Simplifying
6(k + -5) + -1(1 + -5k) = 10k
Reorder the terms:
6(-5 + k) + -1(1 + -5k) = 10k
(-5 * 6 + k * 6) + -1(1 + -5k) = 10k
(-30 + 6k) + -1(1 + -5k) = 10k
-30 + 6k + (1 * -1 + -5k * -1) = 10k
-30 + 6k + (-1 + 5k) = 10k
Reorder the terms:
-30 + -1 + 6k + 5k = 10k
Combine like terms: -30 + -1 = -31
-31 + 6k + 5k = 10k
Combine like terms: 6k + 5k = 11k
-31 + 11k = 10k
Solving
-31 + 11k = 10k
Solving for variable 'k'.
Move all terms containing k to the left, all other terms to the right.
Add '-10k' to each side of the equation.
-31 + 11k + -10k = 10k + -10k
Combine like terms: 11k + -10k = 1k
-31 + 1k = 10k + -10k
Combine like terms: 10k + -10k = 0
-31 + 1k = 0
Add '31' to each side of the equation.
-31 + 31 + 1k = 0 + 31
Combine like terms: -31 + 31 = 0
0 + 1k = 0 + 31
1k = 0 + 31
Combine like terms: 0 + 31 = 31
1k = 31
Divide each side by '1'.
k = 31
Simplifying
k = 31`